The Shtetl and Its Afterlife: Agnon in Jerusalem. Issue 1 (24th April 2017) - Ezrahi, Sidra DeKoven
Abstract : This essay looks at both Buczacz, the Galician hometown of Shmuel Yosef Halevi Czaczkes, and Jerusalem, the adopted city/town of the writer who became S. Y. Agnon, modern Israel's most prominent Hebrew writer and only Nobel Prize winner. Like Jerusalem, the generic shtetl proved over time to be primordial, protean, and portable as a point of reference in Jewish culture and memory. Juxtaposing the "shtetl" as monolithic space with the "city" as heterogeneous space in sociological as well as artistic representations, I argue for a reading of several of S. Y. Agnon's major fictions that render Buczacz and Jerusalem as mirror images of each other. Finally, I gesture towards the ethical and political implications of this move for Agnon's readers and the citizens of Jerusalem.